Architectural Typology Of Mesopotamian Civilization From Ancient Cultural Myth - Khalil, Kadhim Fathel (2013)
Some facts can be easily inferred subjectively but difficult to prove objectively, thus causing the philosophers who came before Socrates to deviate from logic in interpreting the nature of the physical world around them. The dialectic between subjectivity and objectivity is the force that motivated us to restore the symbolic dimensions of Mesopotamian cultural and architectural products. The most important theoretical presentations of architecture are those that deal with the metaphysical and physical environments, which together form the contemporary cultural identity. The most important dialectics in contemporary architectural society in Mesopotamia–Iraq are related to the importance of formulating the basis of cultural identity by highlighting the importance of studies that focus on the Mesopotamian cultural environment. No civilization is older than Mesopotamia, and the cultural and architectural products of this society have extended spatially and temporally but are incapable of speaking for themselves, which lends difficulty to understanding the interpretations of the mental expressions that stand behind the material expressions. As a result, a kind of ambiguity exists about the nature of knowledge relative to its origin in terms of the reflection of mental expressions on architectural expressions. This study sets off from a consideration of cultural and architectural products as part of the philosophical perspective. Therefore, the intellectual exploration of the architectural prototype appears to be the abstract level that is connected to mental expressions on one hand and architectural expressions on the other. The inquiry is phenomenologically unknown; thus, a methodological inquiry was applied by based on the path of formation comprising the spirit of the age and the path of abstraction comprising the cultural species. Thus, this study first adopted the structural analysis method considering the nature of the Mesopotamian cultural core to identify the structure of its mental expressions. Such expressions are represented by myth of creation in Mesopotamia, which is based on the structure of origin, evaluation, and organization. Second, this study adopted the geometrical analysis method to determine the structure of the architectural expressions, which are represented by symbolic architecture, temples, and palaces in Mesopotamia based on the structure of the whole–part, public–private, and mass–void.